Signs and symptoms of temporomandibular disorder and patients' satisfaction before and after orthognathic surgery - Edmar Ricardo Pozzobon Christovam; Eloisa Marcantonio Boeck; Silvia Amélia Scudeler Vedovello; Heloisa Cristina Valdrighi; Viviane Veroni Degan; Mário Vedovello Filho (Universidade Estadual de Campinas, 2017)
Aim: To evaluate signs and symptoms of temporomandibular joint disorder and satisfaction in patients before and after orthognathic surgery. Methods: The sample consisted of 15 patients aged between 19 and 47 years old, indicated for orthodontic-surgical treatment. All patients answered na anamnesis questionnaire based on Helkimo Anamnestic Index to evaluate subjective symptoms and underwent a clinical evaluation based on Helkimo Disfunction Index, applied at three time points: before (T0), three (T1) and six months (T2) after surgery. Statistical models used were χ2 test (Chi-square), Tukey test, confidence interval and analysis of variance (ANOVA). Results: Statistical analysis revealed no significant difference in the incidence of joint sounds, maximum mouth opening, deviation of mouth opening and pain in the TMJ region (p>0.05). No patient presented worsening of the symptomatology. As regards muscular pain, there was a statistically significant improvement with time (p<0.05) and 86.7% of patients reported that they were satisfied with the obtained results. Conclusions: Improvement of TMD after orthognathic surgery may not be the result of correcting malocclusion and satisfaction with the results can be a factor of TMD improvement.